The Effect of Ostracism Workplace on Deviant Behavior with Emotional Exhaustion and Organizational Based Self Esteem as a Mediation Variable - Kemal, Surya Djorgi; Yulivional, Reni; Anggraini, Fivi (SAFE-Network, 2023)
This study aims to analyze the effect of workplace ostracism on deviant behavior with emotional exhaustion and organizational based self-esteem as mediating variables. This research was conducted on all employees of PT Berjaya Pet Sumatra Padang. Sampling was carried out using the census method by distributing questionnaires. Data analysis was performed using path analysis which was processed using PLS software. Based on the results of hypothesis testing, it was found that workplace ostracism had a positive effect on deviant behavior. Emotional exhaustion has a positive effect on deviant behavior. In addition, the research results also found that organizational based self-esteem also had a negative effect on deviant behavior. If it is observed from the mediation effect test, it is found that emotional exhaustion and organizational based self-esteem are able to mediate the relationship between workplace ostracism and deviant behavior in employees of PT Berjaya PT Sumatra Padang.